2019
DOI: 10.15560/15.3.379
|View full text |Cite
|
Sign up to set email alerts
|

New record of Brachycephalus fuscolineatus Pie, Bornschein, Firkowski, Belmonte-Lopes & Ribeiro, 2015 (Anura, Brachycephalidae) from Santa Catarina state, Brazil

Abstract: Brachycephalus fuscolineatus Pie, Bornschein, Firkowski, Belmonte-Lopes & Ribeiro, 2015 was described from Morro do Baú, Santa Catarina, Brazil. This species occurs at elevations of 640-790 m, and it is known to have an extent of occurrence of 23.63 ha. Here, we report a new record of B. fuscolineatus from Morro Braço da Onça, Luiz Alves, Santa Catarina. We recorded it on 21-22 December 2018 at elevations between 525 and 530 m; the new record occupied an area of 0.19 ha. We estimate 9 calling males in 36.35 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…This forest, within the Serra do Mar, occurs in an orographic system of profound topographic and altimetric variation which influences rainfall, insolation, exposure to wind, drainage of water of the soil, microclimate, and the distribution of types of vegetation (de Almeida & Carneiro, 1998; Rizzini, 1997; Veloso et al., 1991). It has been shown that these variations affect the distribution and abundance of Brachycephalus in this region (Bornschein, Firkowski et al., 2016; Bornschein, Ribeiro et al., 2016; Bornschein, Ribeiro et al., 2019; Bornschein, Teixeira et al., 2019; Pie, Ribeiro, et al., 2018; Ribeiro et al., 2017) and, here, we presented evidence that the climate could also play a substantial role the skin morphology of this genus.…”
Section: Discussionsupporting
confidence: 69%
“…This forest, within the Serra do Mar, occurs in an orographic system of profound topographic and altimetric variation which influences rainfall, insolation, exposure to wind, drainage of water of the soil, microclimate, and the distribution of types of vegetation (de Almeida & Carneiro, 1998; Rizzini, 1997; Veloso et al., 1991). It has been shown that these variations affect the distribution and abundance of Brachycephalus in this region (Bornschein, Firkowski et al., 2016; Bornschein, Ribeiro et al., 2016; Bornschein, Ribeiro et al., 2019; Bornschein, Teixeira et al., 2019; Pie, Ribeiro, et al., 2018; Ribeiro et al., 2017) and, here, we presented evidence that the climate could also play a substantial role the skin morphology of this genus.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, we also underscore the absence of records of B. sulfuratus in northern Santa Catarina in some well sampled localities. For example, we obtained no records for B. sulfuratus in Morro Boa Vista (26 30′58″S, 49 03′14″W), on the border between the municipalities of Jaraguá do Sul and Massaranduba, where we described B. albolineatus (Bornschein et al, 2016b), Morro do Baú (26 47′58″S, 48 55′47″W), municipality of Ilhota and Morro Braço da Onça (26 44′58″S, 48 55′41″W), municipality of Luiz Alves, where we report B. fuscolineatus (Ribeiro et al, 2015;Bornschein, Teixeira & Ribeiro, 2019), Morro do Cachorro (26 46′42″S, 49 01′57″W), on the border between the municipalities of Blumenau, Gaspar, and Luiz Alves, where we described B. boticario…”
Section: Additional Information and Declarations Fundingmentioning
confidence: 89%